Emergency Medicine Curriculum: Complications of Pregnancy Small Group Module - Linda L Herman; Kunal Sukhija (eScholarship Publishing, University of California, 2017)
Audience: This curriculum, created and implemented at Kaweah Delta HCD emergency medicine program, was designed to educate our emergency medicine (EM) residents, PGY-1 to PGY-3, as well as medical students and attending physicians. Introduction: Obstetrical (OB) emergencies pose a unique challenge to the EM physician. Given the relative rarity of these presentations within the Emergency Department (ED), it is important that residents are educated in a comprehensive manner to ensure understanding and retention.1 The exact prevalence of emergency department (ED) visits that are associated with complications of pregnancy is unknown, but they are likely a sizeable portion of the patient population of the ED. Also, many hospitals in rural areas have closed their labor and delivery units due to higher operating costs and lack of available medical personnel.2 New models of high-quality teaching that ensure retention of clinically rare, but critical presentations are required. There is a body of research that suggests a small-group discussion model rather than traditional lecture-based content may improve learner engagement and retention. This model encourages active learning, which requires simultaneous instructor and learner engagement.3, 4, 5, 6, 7 Studies have revealed that the application of knowledge through case studies, personal interaction with content experts, and integrated questions are effective learning strategies for emergency medicine.3 The small group discussion classroom is facilitated by content experts with personal experience in the topic at hand. Objectives: We aim to teach the presentation and management of pregnancy complications through interactive teaching during small group discussions concerning patient cases. This curriculum utilizes resources chosen by education faculty, study questions, actual experience, and small group discussions in place of a traditional lecture-based format. In doing so, a goal of the curriculum is to encourage self-directed learning, improve understanding and knowledge retention, improve the educational experience of our residents, and allow assessment by the faculty concerning the knowledge base and ability of the residents. Methods: Core obstetric emergency medicine content will be delivered through small group modules and case-based content authored by faculty and content experts. Suggested resources for self-directed learning are tied to each module. The Socratic Method, as used during small group sessions, drives learner participation and critical evaluation of the core topics. Open-ended questions developed by the faculty andresidents for each module stimulate further discussion and integration with real-life experience. Learners (as well as faculty) are encouraged to utilize free open access medical (FOAM) education resources both in the preparatory self-directed learning phase as well as afterwards to continue integration of core content with real-life experience. Suggested obstetric simulations are included and encouraged as well.